AKU TELAH SEMBUH: Pengalaman Doktrinal Sebagai Kenyataan Sosio-Teologis Pantekosta - Elia Tambunan; Sang Putra Immanuel Duha (Sekolah Tinggi Teologi Anugrah Indonesia, 2023)
This article is written in a social research landscape with Pentecostal theology, namely divine healing as an object of study, by using a critical study method of literary sources, including social media. The question to be answered for the academic field in Indonesia is how to modernize theology as a science that integrates with social science. So far there is a scientific problem. The Bible as the main object of study is too focused on the analysis of biblical texts. Science in these institutions seems to be ignorant of social praxis. The Bible contains narratives of the experience, and history of tribes, societies, and nations. We build our meaning of social theories with systematic theology to produce a theoretical framework. The findings,